The Effect of Price, Product Quality and Trust on The Purchase Interest of Amaranthine Signature Products on Customers of Trans Studio Mall Cibubur in 2022 - Febrianto, Endang; Pujiati, Herni (Dinasti International Journal of Management Science, 2025)
This study aims to determine the effect of price, product quality and trust on interest in purchasing Amaranthine Signature products. The data obtained in this study are based on customers at Trans Studio Mall Cibubur who have made purchases of Amaranthine Signature products. This research is a quantitative research, with data collection method using a questionnaire in the form of google form, using a population of 150 respondents. In this study assisted by using the SPSS version 24 program. The results in this study using hypothesis testing including partial t-test and simultaneous F-test, which show that: 1) The price of purchasing interest with t count of 7.626 > 1.982 and a significant value of 0.000 < 0.05, which states that price has a partial effect on buying interest. 2) Product quality on buying interest with at count of 2.210 > 1.982, and a significant value of 0.028 < 0.05, which states that product quality has a partial effect on buying interest. 3) Trust in buying interest with at count of 4,060 > 1,982 and a significant value of 0.000 < 0.05, which states that trust has a partial effect on buying interest. 4) Price, product quality and trust simultaneously have a significant effect on purchasing interest with F-count 208.713 > 0.03 and a significant value of 0.000 < 0.05.